1997
DOI: 10.1002/art.1780400211
|View full text |Cite
|
Sign up to set email alerts
|

Growth factor regulation of chondrocyte integrins. Differential effects of insulin‐like growth factor 1 and transforming growth factor β on α1β1 integrin expression and chondrocyte adhesion to type VI collagen

Abstract: Objective. The ability of growth factors to modulate integrin expression may be important with regard to processes involved in tissue repair and remodeling. This study was undertaken to determine the effect of transforming growth factor β (TGFβ) and insulin‐like growth factor 1 (IGF‐1) on chondrocyte β1 integrin expression and integrin‐mediated adhesion to extracellular matrix proteins. Methods. Chondrocytes obtained from normal bovine articular cartilage were cultured in the presence or absence of 10% fetal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(74 citation statements)
references
References 26 publications
3
69
0
2
Order By: Relevance
“…8 In combination with TGF β, IGF-1 has a stimulatory effect on the adhesion of chondrocytes to fibronectin and collagen type II. 9 It is important to ensure the controlled delivery of biomolecules, like IGF-1, to avoid adverse effects. Nano-sized carriers (nanoparticles) are considered an attractive tool for this, as nanoparticles are small in dimension, offer a high surface area to volume ratio, and enable targeted drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…8 In combination with TGF β, IGF-1 has a stimulatory effect on the adhesion of chondrocytes to fibronectin and collagen type II. 9 It is important to ensure the controlled delivery of biomolecules, like IGF-1, to avoid adverse effects. Nano-sized carriers (nanoparticles) are considered an attractive tool for this, as nanoparticles are small in dimension, offer a high surface area to volume ratio, and enable targeted drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…These data demonstrate a substrate dependent, significant increase in the migration o f chondrocytes isolated from young articular cartilage in response to TGFpi when coated onto fibronectin [P<0.005] (see fig.2.13a). As previously stated for IGF-1, TGFpi has also been shown to increase a 5 p i expression and in doing so increase adhesion to fibronectin (Loeser, 1997 Rosselot et al, 1994;Tsukazaki et al, 1994;Yaeger et al, 1997) and that TGFpi can increase the expression o f IGF-IRs by chondrocytes (Tsukazaki et al, 1994). A recent study demonstrated that this interaction occurs in situ during periosteal chondrogenesis (Fukumoto et al, 2003).…”
Section: Investigating the Chemotactic Effects O F Igf-1 And Tgfpi Onmentioning
confidence: 63%
“…As interactions between fibronectin and chondrocytes is pi integrin dependent it is interesting to link research suggesting potential synergy between the IGF-1R and the p i integrin subunit by activation o f cell signalling proteins such as She (Shakibaei et al, 1999). IGF-1 has been shown to also increase levels o f the fibronectin specific receptor a 5 p l leading to increased adhesion (Loeser, 1997). No enhanced migration was seen with chondrocytes isolated from young articular cartilage seeded onto type II collagen or aggrecan (see fig.2.13a).…”
Section: Investigating the Chemotactic Effects O F Igf-1 And Tgfpi Onmentioning
confidence: 99%
“…The regulation of chondrocyte integrin function is important in the homeostasis of cartilage as well as in disease states in which interactions between chondrocytes and their ECM are altered. Factors that modulate chondrocyte ECM synthesis, such as IGF-1 and TGF-, also appear to modulate integrin-mediated attachment of chondrocytes to ECM proteins (Loeser 1994(Loeser , 1997. The effects of IGF-1 and TGF-on chondrocyte integrin expression and function, however, in vivo may depend on the relative levels of each growth factor present and thereby providing a means for sophisticated control of cell-matrix interactions in cartilage.…”
Section: Integrinsmentioning
confidence: 99%